A new species of Pseudosinella from Portugal (Insecta : Collembola). XVIIth contribution. - Da Gama, M M (REVUE SUISSE DE ZOOLOGIE, 2004)
Pseudosinella angelae sp. n. is described from a typical Mediterranean landscape dominated by Quercus suber L. in the surroundings of Lisbon. Morphological comparison with similar species is made, in order to establish the genealogical position of the new species.
Keywords: Collembola; Insecta; new species; Portugal; Pseudosinella

Hymenoptera reared from Plagiotrochus suberi (Hymenoptera: Cynipidae) galls in California - Zuparko, R L (Pan-Pacific Entomologist, 1996)
Nine species of Hymenoptera were reared from stem galls induced by Plagiotrochus suberi Weld on Quercus suber L. in Albany, California. The most numerous species reared was P. suberi, but Euderus crawfordi Peck was the most common parasitoid reared. Other species reared were: Aprostocetus pattersonae (Fullaway), A. sp. nr. verrucarii (Balduf), Acaenacis taciti (Girault), Sycophila wiltzae(Balduf), Sycophila sp, possibly foliatae (Ashmead), Brasema sp. and Ceraphron sp. The rearings of all parasitoids (except E. crawfordi and S. wiltzae) constitute new host records. All described parasitoid species are native to North America and represent new associations with the introduced P. suberi.
Keywords: associations; Euderus crawfordi; Insecta; new; Parasitoids; Plagiotrochus suberi; Pragas e doenças do sobreiro - Plagiotrochus suber; Quercus suber

Comparison of Spatial Distribution Patterns of Dung-Feeding Scarabs (Coleoptera: Scarabaeidae, Geotrupidae) in Wooded and Open Pastureland in the Mediterranean “Dehesa” Area of the Iberian Peninsula - GALANTE, E; GARCIA-ROMAN, M; BARRERA, I; GALINDO, P (Environmental Entomology, 1991)
The seasonal and spatial distributions of dung-feeding scarabs in an open pastureland and in wooded (holm oak) pastureland in a typical Mediterranean area of the western part of the Iberian Peninsula (Salamanca) were compared. Six pitfall traps baited with bovine dung were placed in each habitat according to a model by J. P. Lumaret. Only beetles in the families Scarabaeidae and Geotrupidae were studied because they are the most important agents in the elimination of cattle dung from the soil surface. Weekly trapping for 1 yr produced 6,909 specimens. Of the 18 species found, the largest beetles and biomass were concentrated mainly in the wooded habitat, especially in the summer. This constitutes a problem for dung removal because large amounts of dung remain in open pasturelands, possibly resulting in the impoverishment of such areas.
Keywords: dung beetles; Geotrupidae; Insecta; Scarabaeidae